Implementasi Program Dumisake dan Dinamika Politik Pembangunan Daerah: Studi Kebijakan Umkm di Kecamatan Rimbo Bujang - Jaya, Mulia; Epriadi, Dedi; Sari, Marisa Dewi Kurnia (Universitas Muara Bungo, 2025)
This study analyzes the implementation of the Dumisake Program as a public policy initiative for empowering Micro, Small, and Medium Enterprises (MSMEs) in Rimbo Bujang District, Jambi Province. Initiated by the provincial government, the program aims to accelerate post-pandemic economic recovery through direct capital assistance to targeted MSME groups. Using a descriptive qualitative approach and case study method, this research explores the program's input, process, and output stages, as well as the local political dynamics that shape its implementation. Findings reveal persistent challenges, including weak MSME data systems, opaque beneficiary selection, limited training and mentoring, and the prevalence of political patronage influencing aid distribution. These structural and political barriers hinder the program's empowerment objectives. The study recommends reforming program management through digital MSME data development, performance-based evaluation systems, and participatory, accountable governance. With a collaborative governance approach, the Dumisake Program has the potential to serve as a replicable model for inclusive and sustainable grassroots economic policy.